A Pedagogia dos Letramentos e a Análise Crítica de Gênero como suporte teórico de uma unidade didática produzida por professores em formação inicial no projeto Línguas no Campus (LinC) - Pereira, Gabriele Almeida de Moraes (2024)
This research aims to investigate how scientific knowledge is materialized in the development of didactic material by UFSM English Major undergraduates, who participate in the outreach project LinC. Through this investigation, we intended to contribute to the critical development of teachers in initial education, concerning their concepts of language and teaching materialized in didactic materials, regarding the Literacy Pedagogy (KALANTZIS; COPE; PINHEIRO, 2020) and Critical Genre Analysis (CGA) contributions to pre-service teacher education. In this sense, the corpus of this research consists in a didactic unit (DU) entitled “Travel Experiences”. In order to discuss to what extent, the theoretical perspectives that underlie LinC's practices are materialized in the DU, first, we looked at the Presentation and Syllabi sections looking for linguistic clues that could confirm the language approach as social practice. In the Presentation, the focus was on the practices that would be explored in contrast to the lexico-grammatical aspects that allowed these to be carried out. In relation to the Syllabi, we found that it aligns with the language stratification (MOTTA-ROTH, 2008), exploring the levels 'Discourse: Ideology', 'Genre: Context of Culture', 'Register: Context of Situation' and 'Lexicogrammar', not just covering the 'Phonology and Graphology' levels. Secondly, we analyzed the selected texts in terms of authenticity and multimodal elements, as well as their connection throughout the DU. The genres and texts explored in it are authentic and organized in a meaningful way, as they explore practices that characterize an academic trip and are linked in a chronological and meaningful way. Aiming to identify the proposed literacy practices, we identified, from the statements, all knowledge processes, with the exception of “Applying Creatively”. Therefore, “critical” and “functional” pedagogies were considered the focus of the DU, as the activities explore the meanings of the texts, as well as provide space for the production of meaning and critical thinking by the students. “Didactic” and “authentic” pedagogies are also explored, promoting immersion in new possible practices and contextualizing DU proposals based on students’ experiences and prior knowledge. Then, it is possible to conclude that the DU aligns with the LinC perspective, exploring the four pedagogies based on the knowledge processes, however, with an emphasis on functional (38.03%) and critical (32.6%) pedagogies, which illustrate the focus on practices mediated and problematized by language, rather than a more structuralist focus, suggested by didactic (29.33%) and authentic (16.30%) pedagogies. However, we understand the DU should underground future chances, as the ways of producing meanings are in constant development. To contribute with these further adaptations, we propose, by the end of the discussion, some pedagogical propositions to explore the process of applying creatively, as well as to enrich the travel experiences proposed along the DU.